Local Referral of High-risk Patients to High-quality Hospitals: Surgical Outcomes, Cost Savings, and Travel Burdens. Issue 6 (June 2020) - Smith, Margaret E.; Shubeck, Sarah P.; Nuliyalu, Ushapoorna; Dimick, Justin B.; Nathan, Hari
Abstract : Objective: We sought to assess the potential changes in Medicare payments and clinical outcomes of referring high-risk surgical patients to local high-quality hospitals within small geographic areas. Summary Background Data: Previous studies have documented a benefit in referring high-risk patients to high-quality hospitals on a national basis, suggesting selective referral as a mechanism to improve the value of surgical care. Practically, referral of patients should be done within small geographic regions; however, the benefit of local selective referral has not been studied. Methods: We analyzed data on elderly Medicare beneficiaries undergoing any of 4 elective inpatient surgical procedures between 2012 and 2014. Hospitals were categorized into Metropolitan Statistical Areas by zip code and stratified into quintiles of quality based on rates of postoperative complications. Patient risk was calculated by modeling the predicted risk of a postoperative complication. Medicare payments for each surgical episode were calculated. Distances between patients' home zip code and high- and low-quality hospitals were calculated. Results: One quarter of high-risk patients underwent surgery at a low-quality hospital despite the availability of a high-quality hospital in their small geographic area. Shifting these patients to a local high-quality hospital would decrease spending 12% to 37% ($2, 500 for total knee and hip replacement, $6, 700 for colectomy, and $11, 400 for lung resection). Approximately 45% of high-risk patients treated at low-quality hospitals could travel a shorter distance to reach a high-quality hospital than the low-quality hospital they received care at. Conclusions: Complication rates and Medicare payments are significantly lower for high-risk patients treated at local high-quality hospitals. This suggests triaging high-risk patients to local high-quality hospitals within small geographic areas may serve as a template for improving the value of surgical care.